2017
DOI: 10.1111/fcsr.12203
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Influence on Retirement Planning in Malaysia

Abstract: Many studies have indicated that the development of children's behavior is strongly influenced by their parents’ behavior during childhood. This paper applied the theory of planned behavior as a basis for the analysis of data from a sample of 520 Malaysians aged 18 and over. Regression analysis was used to assess the relationship between parents’ financial behavior and their children's retirement planning. Results showed that: (a) parents play a significant role as agents of financial socialization for their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
0
13
0
6
Order By: Relevance
“…However, Filipiak and Walle, (2015reported marital status to be an insignificant predictor of financial literacy. Finally, in the context of race in Malaysia, Kimiyaghalam et al (2017) found Chinese have more level of financial literacy followed by Malay among the three ethnic groups. Similarly, Au and Tan (2018) found that there is an association between financial literacy with ethnic group in Malaysia.…”
Section: Socio-demographic Factorsmentioning
confidence: 89%
“…However, Filipiak and Walle, (2015reported marital status to be an insignificant predictor of financial literacy. Finally, in the context of race in Malaysia, Kimiyaghalam et al (2017) found Chinese have more level of financial literacy followed by Malay among the three ethnic groups. Similarly, Au and Tan (2018) found that there is an association between financial literacy with ethnic group in Malaysia.…”
Section: Socio-demographic Factorsmentioning
confidence: 89%
“…Next, path coefficient results indicated that retirement planning has a significant positive relationship on retirement village buying intention, which suggested that strategic retirement planning will increase the likelihood of buying a retirement village unit. Planning and saving in advance of retirement will assist the elderly to enjoy a comfortable living during their old ages (Kimiyaghalam et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, being unprepared for retirement is another pain of this segment because young people think it is too early to plan for retirement. Consequently, individuals who lack retirement preparedness are more likely to have retirement unreadiness (Kimiyaghalam et al 2017). "I'm not prepared for retirement yet because I think it's too soon.…”
Section: Interviewee Intervieweementioning
confidence: 99%